Experience in the Application of Hybrid Ceramic Restorations in the Cervical Region - Dorofeev, A.E. (Asian Journal of Pharmaceutics (AJP), 2018)
A variety of diseases in the cervical region of the teeth forcing dentists to move to the selection of material for treatment based on the leading etiological factor in the defeat. Manufacturers offer for the restoration of this group of diseases of SIC, composites and hybrid ceramics (VITA), which combines the positive properties of traditional ceramics and composites for computer-aided design/computer-aided manufacturing (CAD/CAM). VITA ENAMIC is a middle ground: A natural elasticity as dentin, as well as abrasive properties similar to the natural enamel. In this clinical case, successful restoration of the cervical defect of the tooth is presented 2.4, using VITA ENAMIK and CAD/CAM technology. The tooth was isolate by the cofferdam system. Treatment of the tooth was carry out with the help of aluminum oxide. The fixation was carried out by adhesive technology using the Variolink II Professional Set (Ivoclar Vivadent). After that, the final treatment was carry out using a special kit.